1 1 − 2 = 3 2 1 1 1 1 − 2 2 = 3 3 2 1 1 1 1 1 1 − 2 2 2 = 3 3 3 2
True or False?
2 n 1 1 … 1 − n 2 2 … 2 = ( n 3 3 … 3 ) 2 , for all positive integers n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L H S = 2 n 1 1 1 ⋯ 1 − n 2 2 2 ⋯ 2 = 9 1 0 2 n − 1 − 2 ( 9 1 0 n − 1 ) = ( 3 1 0 n ) 2 − 9 1 − 2 ( 3 1 0 n ) ( 3 1 ) + 9 2 = ( 3 1 0 n ) 2 − 2 ( 3 1 0 n ) ( 3 1 ) + 9 1 = ( 3 1 0 n − 3 1 ) 2 = ( 3 9 9 9 ⋯ 9 n ) 2 = ( n 3 3 3 ⋯ 3 ) 2
True , L H S = R H S .
Problem Loading...
Note Loading...
Set Loading...
Starting from the left hand side of the equality and considering the decimal expansion of the numbers, we get:
2 n 1 1 … 1 − n 2 2 … 2 = ( 1 0 2 n − 1 + 1 0 2 n − 2 + … + 1 0 + 1 ) − 2 × ( 1 0 n − 1 + 1 0 n − 2 + … + 1 0 + 1 )
= 1 0 − 1 1 0 2 n − 1 − 2 × 1 0 − 1 1 0 n − 1 = 9 1 × ( 1 0 2 n − 2 × 1 0 n + 1 )
= 9 1 × ( 1 0 n − 1 ) 2 = 9 × ( 1 0 − 1 1 0 n − 1 ) 2
= 9 × ( n 1 1 … 1 ) 2
= ( n 3 3 … 3 ) 2
Hence, the statement is both beautiful and true .